Design and Implement a Wearable Device for Visually Impaired People - Tran, Hai Nam; Nguyen, Minh Duc; Do, Hanh (Old Journal, 2018)
Braille language and white cane are the especially important tools in visually impaired people's life. Braille helps visually impaired people learn, work and update information to integrate them into normal social life. White cane assists them to walk confidently without supporting from other people. In this paper, we propose a wearable device for visually impaired people which is able to communicate with smartphone via Bluetooth connection to send or receive information, then display that information by Braille language. In addition, this device also has the moving assistance function for the visually impaired by detecting obstacles and guiding them to return to their way after passing those obstacles.